2010
DOI: 10.1302/0301-620x.92b1.21530
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year results of a double-heat-treated metal-on-metal hip resurfacing

Abstract: Second-generation metal-on-metal bearings were introduced as a response to the considerable incidence of wear-induced failures associated with conventional replacements, especially in young patients. We present the results at ten years of a consecutive series of patients treated using a metal-on-metal hip resurfacing. A distinct feature of the bearings used in our series was that they had been subjected to double-heat treatments during the post-casting phase of their manufacture. In the past these bearings had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 35 publications
0
44
0
5
Order By: Relevance
“…Ten-year clinical and survivorship results of metal-onmetal hip resurfacing have been reported [6,14,16,39] but are still not available from a majority of centers performing this type of surgery. Also, of the three reports with 10-year data, only two used currently available devices [6,39].…”
Section: Discussionmentioning
confidence: 99%
“…Ten-year clinical and survivorship results of metal-onmetal hip resurfacing have been reported [6,14,16,39] but are still not available from a majority of centers performing this type of surgery. Also, of the three reports with 10-year data, only two used currently available devices [6,39].…”
Section: Discussionmentioning
confidence: 99%
“…The extremely low incidence of component loosening in our series shows that fixation problems have largely been solved in the BHR in contrast to the loosening reported [18] with the Durom resurfacing device (Zimmer, Swindon, UK). In addition to failures due to reasons such as infection, resurfacings fail through one of two modes, mechanical failures such as femoral neck fractures and bearing-related failures such as failures due to osteolysis [19], soft tissue reactions and periarticular necrosis [20]. These can occur due to one of three risk factors: patient-related, surgeon-related and implant-related.…”
Section: Discussionmentioning
confidence: 99%
“…The many nuances [32] of implant design and materials constitute the third risk factor for resurfacing failures. Our past experience [19] has shown that changes to materials processing can be detrimental to implant survivorship. More recently the consistently poor performance of the ASR device (Johnson & Johnson DePuy Ltd., Leeds, UK) was shown to be due to unfavourable design features such as the low angle of articulation and reduced diametral clearance [16].…”
Section: Discussionmentioning
confidence: 99%
“…Both positive [2,11] and negative reports [25,34,35,37,61] have emerged with regard to using MoM bearings. There are likely many risks that could trigger a need for MoM revision.…”
Section: Introductionmentioning
confidence: 99%